Immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination in patients receiving secukinumab: a literature review - Gisondi, Paolo; Simon, David; Alarcon, Ivette; Pournara, Effie; Puig, Lluís (Journal of Dermatological Treatment, 2023)
Purpose: There is a paucity of evidence on the impact of immune-mediated inflammatory disease (IMID) treatments on the immunogenicity of SARS-CoV-2 vaccination. The purpose of this literature review is to address the question of whether patients with IMIDs receiving secukinumab, a fully human anti–interleukin-17A monoclonal antibody, have an adequate immune response after SARS-CoV-2 vaccination. Materials and Methods: Clinical studies that evaluated the effect of secukinumab on immune responses in patients with IMIDs after SARS-CoV-2 vaccination were searched in publication databases, including Medline and Embase, until May 2022. Results: From the 53 articles identified, a total of 11 articles were included. Overall, the majority of the patients treated with secukinumab elicited an adequate immune response to SARS-CoV-2 vaccines. Patients receiving secukinumab for IMIDs developed cellular immune responses following vaccination with the BNT162b2 vaccine, and there were no significant differences in the overall humoral and cellular immune responses between patients and healthy individuals. The third dose of the BNT162b2 mRNA vaccine resulted in a positive antibody response in secukinumab-treated patients. Conclusion: The available data provide no evidence of impairment in immunological response to SARS-CoV-2 vaccines by secukinumab in patients with IMIDs.
CRIS-Team Scopus Importer:2023-02-10
Keywords: COVID-19; immune-mediated inflammatory diseases; SARS-CoV-2 vaccination; secukinumab